Pemikiran Ibnu Rusyd dalam Mengonsep Negera yang Ideal: Studi Kajian Kepustakaan - Muhammad Fajar Pramono; Haila Fardyatullail (Madania: Jurnal Ilmu-Ilmu Keislaman, 2022)
This researcher aims to analyze Ibn Rushd's thoughts about the Ideal State. This research uses the literature study method by collecting data from various reports in the form of books, articles, official records, and others. The collected data are analyzed with the aim of creating a systematic, factual, and accurate picture of the object under study.  With this method, the researcher found several important points in the ideal state according to Ibn Rusyd; First, the Ideal State is not seen in terms of its physique or its buildings, but from the strength of its human soul. If the human soul is good then, the state will be good. And if the human soul is corrupted then, the state will be damaged. Secondly, Man is a social being, who needs help from others to help him and meet his needs. With this, Man will not be able to live alone. In addition, Man is the Being of Allah Swt who was created to recognize Him by submitting to the laws of Allah Swt in living life on Earth, whether man's relationship with God or man's relationship with a man. Third, leadership characteristics are good character, love of science, education, honesty, physical strength, and being a philosopher, because the leader has an important role, namely as a regulator of world affairs and maintaining religion.